Psychological, Social and Health-Related Challenges in Spanish Older Adults During the Lockdown of the COVID-19 First Wave - Rodríguez-González, Raquel; Facal, David; Martínez-Santos, Alba-Elena; Gandoy-Crego, Manuel (Frontiers in Psychiatry, 2020)
Background: The global pandemic of COVID-19 has required a population lockdown. Spain has one of the oldest/most aging populations in the world and was one of the most affected countries. We aim to describe the psychological and social implications as well as health-related behaviors as a result of the lockdown in community-dwelling older adults. Materials and methods: Observational cross-sectional study. A total of 528 participants of over 60 years of age were recruited using snowball sampling technique during the lockdown of the COVID-19 first wave using an anonymous self-administered questionnaire composed of descriptive questions and validated scales for resilience (Brief Resilient Coping Scale) and emotions (Scale of Positive And Negative Experience). Results: Most participants (76.9%) live with other people and have an open space at home (64%). Only 33.7% continued doing activities to promote healthy aging, 65.7% did less physical activity and 25.6% increased their intellectual activity. Most of them (83%) used electronic communication with family and friends to a greater extent, and left the house to run basic errands. Greater scores on resilience showed significant negative correlations with age and negative feelings, and positive correlations with the size of the social network and positive feelings. Lacking an open space at home was associated with more negative feelings. Discussion: Older people are a vulnerable group severely affected by this pandemic crisis at multiple levels, requiring specific interventions to minimize the effects of changes in lifestyle that may be harmful. Detecting needs is essential to improve care and support from community health and social services, both nowadays and in future similar situations.